Philosophical content and essence of the formation of a culture of peace in youth - Ilimjon Abdukhamjonovich Abdumalikov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This scientific article is written about the philosophical content of the formation of a culture of peace of youth in the world as a result of current scientific research and in the era of globalization.